2018
DOI: 10.1039/c8ra01657g
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the treatment of realN,N-dimethylacetamide contaminated wastewater using a membrane bioreactor and its membrane fouling implications

Abstract: Treatment ofN,N-dimethylacetamide (DMAC) wastewater is an important step in achieving the sustainable industrial application of DMAC as an organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…During wastewater treatment, membrane fouling of MBR was mainly caused by EPS. 42 The main components of EPS were proteins and polysaccharides, etc. 43,44 The higher the protein contents in EPS, the stronger the hydrophobicity of wastewater.…”
Section: Fouling Control Performance Of Tween-20 Coated Pvdf Membranementioning
confidence: 99%
“…During wastewater treatment, membrane fouling of MBR was mainly caused by EPS. 42 The main components of EPS were proteins and polysaccharides, etc. 43,44 The higher the protein contents in EPS, the stronger the hydrophobicity of wastewater.…”
Section: Fouling Control Performance Of Tween-20 Coated Pvdf Membranementioning
confidence: 99%
“…Conventional biological nitrification is applicable to low-concentration nitrogenous wastewaters (e.g., NH 4 + -N < 50 mg/L) mainly using the ammoniaoxidizing and nitriteoxidizing bacteria. One study reported that DMAc-contaminate wastewater via bacteria digestion released odor gas ammonia (NH 3 ), and the membrane fouling was inevitable in the membrane bioreactor (MBR) (Zhou et al 2018a). DMAc (C 0 = 200 mg/L) was removed by 95.4% in water solution with a reaction rate constant k = 0.0258 min −1 using CuFe 2 O 4 /O 3 catalyzed-ozone process (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention of submerged fermentation, bioreactors have found wide applications in diverse fields including wastewater treatment in the environmental protection sector, cell culture and tissue engineering in the healthcare sector, the Abbreviations: µSI, micro sequential injection; A/D, analog/digital; AI, artificial intelligence; ALE, adaptive laboratory evolution; BLSS, Bioregenerative Life Support System; CMOS, complementary metal-oxide semiconductor; D/A, digital/analog; DCS, distributed control system; DIY, do-it-yourself; DO, dissolved oxygen; DOE, design of experiment; DoS, denial of service; FCS, fieldbus control system; FF, Foundation Fieldbus; FIA, flow injection analysis; FOCS, flat organizational control system; HSCS, hierarchical structure control system; IoT, Internet of Things; KBCS, knowledge-based control system; MES, manufacturing execution system; MEMS, microelectromechanical system; NCS, networked control system; NIR, near-infrared; OD, optical density; OS, operating system; PAT, process analytical technique; PTR-ToF-MS, proton transfer reaction with a time-of-flight mass spectrometer; PID, proportional-integral-derivative; PLC, programmable logical controller; Pt_rGO, Pt-decorated reduced graphene oxide; RFID, radio frequency identification; UPLC, ultra-performance liquid chromatography; VHM, valve health monitor. production of high-value pharmaceuticals and bulk chemicals in industrial biotechnology, and even the cultivation of algae for oxygen generation in space exploration (Li X. et al, 2016;Pirasaci et al, 2017;Zhuo et al, 2018;Christoffersson and Mandenius, 2019). Strong demand for various applications stimulated progress in bioreactor structure design to fulfill specific purposes, such as solid-state fermentation bioreactors used in the Chinese alcoholic beverage (Baijiu) brewing industry, anaerobic membrane bioreactors for wastewater treatment, classic tank bioreactors used in the fermentation industry, and the recently developed inexpensive single-use bioreactors for the small-scale production of high-value biological pharmaceuticals (Zhuo et al, 2018;Fang et al, 2019;Metze et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…production of high-value pharmaceuticals and bulk chemicals in industrial biotechnology, and even the cultivation of algae for oxygen generation in space exploration (Li X. et al, 2016;Pirasaci et al, 2017;Zhuo et al, 2018;Christoffersson and Mandenius, 2019). Strong demand for various applications stimulated progress in bioreactor structure design to fulfill specific purposes, such as solid-state fermentation bioreactors used in the Chinese alcoholic beverage (Baijiu) brewing industry, anaerobic membrane bioreactors for wastewater treatment, classic tank bioreactors used in the fermentation industry, and the recently developed inexpensive single-use bioreactors for the small-scale production of high-value biological pharmaceuticals (Zhuo et al, 2018;Fang et al, 2019;Metze et al, 2019).…”
Section: Introductionmentioning
confidence: 99%